(untitled) (Academia Science Repository, 2023)
A youngster is raised in a technologically advanced environment in today’s world. This distinctly alters children’s perceptions and learning patterns, establishes the necessity of using engaging digital tools with young children, and inspires them to consciously use their speech and correct behaviors. It will be vital to practice speech restraint. In order to promote conversation about the potential uses of digital technologies, analyze theoretical literature, and correct speech therapy, this paper will concentrate on the usage of pedagogical technology tools employed in preschool institutions.